Knowledge graph based ubiquitous power IoT security visualization technology - Yang YU; Shaomin ZHU; Chaoyi BIAN (Dianxin kexue)
With the construction of the ubiquitous power IoT,the power network transform to interconnection,the data become more interactive and shared,and the business transform to lateral link-up,which pose new challenges to the original network security protection system.Network security visualization technology helps network security personnel quickly identify potential attacks,locate abnormal events,discover new types of attacks,and quickly capture global network security situation by displaying and analyzing the graph patterns.Based on the knowledge graph,the ubiquitous power IoT security analysis was carried out.The internal and external threat intelligence was modeled firstly.Then the relationship between the conceptual entities was constructed.The threat intelligence as knowledge graph was modeled,and then the abstract and complex alarm information which was invisible was converted into a more intuitive and convenient style,which provided accurate support for ubiquitous network security protection decisions in the power IoT.